The effect of percussion massage therapy on the recovery of delayed onset muscle soreness in physically active young men—a randomized controlled trial - Li, Haiwei; Luo, Liang; Zhang, Jing; Cheng, Peipei; Wu, Qiang; Wen, Xinping (Frontiers in Public Health, 2025)
BackgroundDelayed onset muscle soreness (DOMS) is a common condition among physically active individuals, often resulting in reduced performance and discomfort. Although percussive massage treatment (PMT) is widely used as a recovery tool, there is limited evidence supporting its efficacy compared to traditional methods such as static stretching.ObjectiveTo investigate the effect of PMT on recovery from DOMS in physically active young men.MethodsThirty physically active male college students were randomized into three groups: static stretching (SS) group, a short-duration PMT (S-PMT) group, and a long-duration PMT (L-PMT) group. All participants performed squats to induce DOMS, followed by interventions of static stretching, 25 min of PMT, or 40 min of PMT, respectively. Measurements included the visual analog scale (VAS) pain score, knee joint range of motion (ROM), countermovement jump (CMJ), and integrated electromyography (iEMG). These were measured at baseline (P0), post-DOMS protocol (P1), post PMT (P2), 24 h post-intervention (P3), and 48 h post-intervention (P4). Data were analyzed using repeated-measures ANOVA or nonparametric tests, with multiple comparisons conducted at a significance level of p < 0.05.ResultsCompared with the SS and S-PMT group, the L-PMT group at P4 demonstrated significantly greater jump height (SS group: p < 0.001, d = 8.691; S-PMT group: p = 0.006, d = 4.37), peak ground reaction force (SS group: p < 0.001, d = 19.174; S-PMT group: p < 0.001, d = 14.334), and propulsion impulse (SS group: p < 0.001, d = 8.302; S-PMT group: p = 0.003, d = 4.517) during the CMJ propulsion phase. Additionally, the normalized iEMGs of the three muscles in the L-PMT group were significantly lower than those in the S-PMT (VM: p < 0.001, d = −5.692; RF: p < 0.001, d = −8.222; VL: p < 0.001, d = −10) and SS groups at P4 (VM: p < 0.001, d = −12; RF: p < 0.001, d = −11.384; VL: p < 0.001, d = −15). At P4, the L-PMT group exhibited significantly lower VAS scores than the SS group (p = 0.003, d = −1.53), as well as significantly greater knee joint ROM compared to the SS group (p = 0.012,d = 4.77).ConclusionPMT was more effective than static stretching for DOMS recovery. Furthermore, two 40-min PMT sessions provided greater benefits than two 25-min sessions for treating DOMS. These findings suggest that PMT can be a valuable tool for physically active individuals seeking to enhance recovery and maintain performance.Clinical trial registrationThe study was registered on ClinicalTrials.gov on September 21, 2024, with the identifier number NCT06612502.